Dialogical experiences in practice – Research with Danish daycare: Moving from abstract to concrete generalizations. (March 2020) - Hviid, Pernille
The project investigated the development of more sustainable managerial practices than the widespread New Public Management. The concrete case concerned the public Danish daycare sector and included all groups of actors (children, pedagogues, parents, Centre leaders, administration and politicians) aiming at inventing structures and practices, which could support and preserve 'the good daycare'. An analysis of the existing practices showed that the system in all its layers and interconnections predominantly was built on static ontologies. This included the guiding principles for children's learning and development, the educational programmes and manuals as well as the formats of documentation and evaluation. Ambitiously, we suggested a change towards a processual ontology, in which dialogues between all groups fed into the establishment of a new managerial order, built on multi-voiced meaningful premises. We thus aimed at supporting the construction of new kind of knowledge, moving from abstract generalized to concrete generalized . The concrete generalized evolved through dialogues and interactions as collaborative strategies, guiding conceptualizations and procedures as well as a common care for the 'we' and the object of the shared attention: The good daycare. These processes are presented and discussed in the paper.